Challenges of Scientific Research in the Humanities and Social Sciences in Libyan Universities: A Field Study on Faculty Members at the University of Gharyan - Alsonni, Fathi Ramadan (Sharwes Scientific Journal, 2026)
The study aims to identify the challenges and obstacles facing scientific research in the humanities and social sciences from the perspective of faculty members in the Faculties of Arts and Education at the University of Gharyan (Gharyan and Mizda). It also seeks to propose recommendations and solutions to enhance scientific research in line with global developments. The researcher adopted the descriptive-analytical method, using a questionnaire that was designed, validated, and distributed to all faculty members in the selected faculties through a comprehensive survey approach, along with appropriate statistical analysis. The significance of the study lies in the fact that these faculties serve as a primary source of educational and academic personnel for various state institutions. The results revealed that the quality of scientific research in the targeted faculties is below the desired level. The main obstacles include cognitive, financial, administrative, and personal challenges, in addition to the absence of a clear strategic vision and well-defined research policies, as well as limited funding for research activities .The findings further indicate that improving scientific research depends on addressing these challenges. Accordingly, the study recommends developing clear strategic plans and programs, increasing financial support, and providing a stable and supportive environment that encourages research and innovation and ensures the requirements of high-quality scientific research.